Adding lysine and yeast extract improves sensory properties of low sodium salted meat. (January 2020) - Vidal, Vitor A.S.; Santana, Jaqueline B.; Paglarini, Camila S.; da Silva, Maria A.A.P.; Freitas, Mônica Q.; Esmerino, Erick A.; Cruz, Adriano G.; Pollonio, Marise A.R.
Abstract: The partial reduction of Sodium Chloride (NaCl) and the use of lysine, yeast extract and substitute salts Potassium Chloride (KCl) and Calcium Chloride (CaCl2 ) in the characteristics of salted meat was investigated. Proximate composition, physicochemical properties (pH, water activity, lipid oxidation), instrumental analysis (color, shear force), microbiological analysis (total counts, lactic acid bacteria counts, thermally tolerant coliforms, and total coliforms) and sensory evaluation (120 consumers) were performed. The partial replacement of NaCl by KCl and CaCl2 significantly reduced the sodium content of salted meat treatments, while lysine and yeast extract minimized the negative sensory effects due to the addition of KCl and CaCl2 . The addition of lysine and yeast extract increased the sensory acceptance and decreased rancid aroma, salty taste, and aftertaste of salted meat made with a blend of NaCl + KCl + CaCl2, with no differences in the physiochemical quality parameters. Moreover, the treatments made with the blend NaCl + KCl exhibited characteristics similar to traditional salted meat formulations. Highlights: Use of lysine, yeast extract, KCl and CaCl2 to reduce sodium content in salted meat The addition of lysine and yeast extract increased the sensory acceptance. Lysine and yeast extract minimized the rancid aroma, salty taste and aftertaste.